Shelley C. Stone, Morgantina Studies 6. The Hellenistic and Roman Fine Pottery - Stone, Peter J. (Journal of Hellenistic Pottery and Material Culture, 2020)
This is the sixth volume reporting the results of the Morgantina excavations in Central Sicily and the first to deal primarily with pottery. The Morgantina excavations operated from 1955–1971 under the auspices of Princeton University and the University of Illinois and from 1980 to the present under the University of Virginia. While originally conceived of as a volume covering all the Hellenistic and Roman pottery and lamps, constraints of space and time necessitated a two-part division, with a volume on plain pottery, cooking wares, and lamps to follow.